The challenge of sarcomas: the patient advocacy group perspective - Wilson, Roger (Clin Sarcoma Res, 2019)
BACKGROUND: The patient advocacy agenda covers every aspect of cancer treatment and care. This inevitably means that this review covers almost everything that patient advocates are involved with, whether locally, nationally or across national borders. Over more than 15 years of working as an advocate I have been involved in representation and/or discussion about almost all the topics which follow. STRUCTURE OF THE REVIEW: I have broken this review into five main sections and have identified within each an advocacy priority. This is then supported by a number of further areas of advocacy activity. The review starts with a look at what advocacy is and closes with a short discussion on how sarcoma advocacy is structured internationally. The five sections are: (i) Clinical challenges, (ii) Challenges for healthcare systems, (iii) The cross-border challenges, (iv) Keeping up to date, (v) Research. The five priority challenges, one within each area above, are listed respectively in order with the above: (i) Earlier accurate diagnosis and primary treatment, (ii) Multi-Disciplinary Management, (iii) Cancer registration and patient data, (iv) Quality of life and PROs, (v) Patient involvement. CONCLUSIONS: Across many of the challenges which I identify good progress is being made. The importance of the partnership with the professional specialists in treating sarcoma cannot be emphasised too strongly and the leadership of key people, whether patient advocates or professionals, is acknowledged. There are challenges indicated which have yet to be properly addressed. Inevitably some of them have characteristics which make them especially problematic and they tend to drop lower on everyone’s agendas. This does not mean we should forget them.